The Effectiveness of Employee Performance at the Office of PT. Yodya Karya (Persero) Region II Makassar - Khairunnisa, Putri; Niswaty, Risma; Darwis, Muh (Pendidikan Administrasi Perkantoran, UNM, 2025)
This study aims to determine the Effectiveness of Employee Performance at the Office of PT. Yodya Karya (Persero) Region II Makassar. The approach and type of research used are qualitative research approaches and descriptive research types, where the informants are employees in the field of marketing and employees in the field of operations. The data collection technique carried out was using observation, interview, and documentation methods. The data analysis techniques used are data condensation, data presentation, and conclusion drawn. The results of this study show that all indicators used in the research on the Effectiveness of Employee Performance in the Office of PT. Yodya Karya (Persero) Region II Makassar is relatively good. The indicator in question is the quality of work which is classified as good because employees are able to complete work on time by working in a team and dividing responsibilities, so that work can be completed effectively. The quantity of work is classified as good because employees work with the provisions of SOPs, every target and task completion standard always refers to the SOP. Knowledge of work is classified as a good category where employees understand their duties well and utilize technical knowledge, including advanced technology, to improve work efficiency and effectiveness. Creativity is classified as a good category because employees show innovative behaviour in providing new ideas to solve problems and remain calm so that they are able to find wise solutions. Cooperation is classified as a good category because employees understand the importance of cooperation in the organization to facilitate work and achieve goals, because each team member already has their own roles and responsibilities, as well as respecting differences of opinion, and supporting each other. Steadfastness in work is also classified as good because employees are consistent in working, managing time well, and focused, so that work is completed on time and effectively.